Postoperative Pulmonary Complications in the ENIGMA II Trial: A Post Hoc Analysis. (16th January 2023) - Peyton, Philip J.; Liskaser, Grace; Ho, Alexander; Marsh, Harry; Etherington, Christopher; Torlot, Frederick; Desai, Manisha; Perrett, George; Chee, Brian; Leslie, Kate; Myles, Paul S.
Abstract : Background: Nitrous oxide promotes absorption atelectasis in poorly ventilated lung segments at high inspired concentrations. The Evaluation of Nitrous oxide In the Gas Mixture for Anesthesia (ENIGMA) trial found a higher incidence of postoperative pulmonary complications and wound sepsis with nitrous oxide anesthesia in major surgery compared to a fraction of inspired oxygen of 0.8 without nitrous oxide. The larger ENIGMA II trial randomized patients to nitrous oxide or air at a fraction of inspired oxygen of 0.3 but found no effect on wound infection or sepsis. However, postoperative pulmonary complications were not measured. In the current study, post hoc data were collected to determine whether atelectasis and pneumonia incidences were higher with nitrous oxide in patients who were recruited to the Australian cohort of ENIGMA II. Methods: Digital health records of patients who participated in the trial at 10 Australian hospitals were examined blinded to trial treatment allocation. The primary endpoint was the incidence of atelectasis, defined as lung atelectasis or collapse reported on chest radiology. Pneumonia, as a secondary endpoint, required a diagnostic chest radiology report with fever, leukocytosis, or positive sputum culture. Comparison of the nitrous oxide and nitrous oxide–free groups was done according to intention to treat using chi-square tests. Results: Data from 2, 328 randomized patients were included in the final data set. The two treatment groups were similar in surgical type and duration, risk factors, and perioperative management recorded for ENIGMA II. There was a 19.3% lower incidence of atelectasis with nitrous oxide (171 of 1, 169 [14.6%] vs. 210 of 1, 159 [18.1%]; odds ratio, 0.77; 95% CI, 0.62 to 0.97; P = 0.023). There was no difference in pneumonia incidence (60 of 1, 169 [5.1%] vs. 52 of 1159 [4.5%]; odds ratio, 1.15; 95% CI, 0.77 to 1.72; P = 0.467) or combined pulmonary complications (odds ratio, 0.84; 95% CI, 0.69 to 1.03; P = 0.093). Conclusions: In contrast to the earlier ENIGMA trial, nitrous oxide anesthesia in the ENIGMA II trial was associated with a lower incidence of lung atelectasis, but not pneumonia, after major surgery. Abstract : This study reanalyzed the ENIGMA II data from 10 Australian centers (approximately 33% of the total multinational cohort) to compare the incidence of atelectasis in the two treatment groups. In contrast to the original ENIGMA trial, there was a lower incidence of atelectasis with use of nitrous oxide. There was no effect of nitrous oxide on the secondary outcomes of pneumonia, combined pulmonary complications, or hospital length of stay.